Education and the politics of memory in Russia and Eastern Europe: infested with history - Rumyantsev, Sergey (Routledge contemporary Russia and Eastern Europe series, 2025)
This book examines both formal and extracurricular education, and the politics of memory and historical narratives in Armenia, Azerbaijan, Russia, and Ukraine.